Development of a bidirectional PCR tool for Tenera oil palm (“Elaeis guineensis” Jacq.) identity - Vona D. ODENORE; Geoffrey Obinna ANOLIEFO; Beckley IKHAJIAGBE; Omorefe ASEMOTA; Chukwuemeka R. EKE; Leonard O. IHASE (Studia Universitatis Babeș-Bolyai. Biologia)
Three forms of fruit are distinguished in the Oil palm (Elaeis guineensis Jacq.): Dura, Pisifera and Tenera. The most cultivated high yielding oil palm variety, the thin shell Tenera is produced from the cross between the thick shelled Dura and the shell-less Pisifera. Due to the perennial nature of the oil palm, it is impossible to determine the fruit phenotype until it is reproductively mature. Oil palm farmers are therefore faced with the challenge of uncertainty of the kind of fruits and yield output expected until production time. The recent sequencing of the shell gene in the oil palm made it possible to identify Single Nucleotide Polymorphism (SNP) mutations that are now useful in developing molecular markers for fruit form predictions. In this study, Allele Specific PCR (AS-PCR) was used to assess regions of the shell gene containing SNPs for oil palm fruit form discrimination. Three primer pairs (S1, S2 and S3) were designed as common primers while four AS-PCR primers (S20, S22, S32 and S33) were adopted as inner primers. Possible combinations of common and AS primers were investigated in Dura, Pisifera and Tenera genomes. A 300bp fragment was observed to be unique in the Tenera shell gene when S3 was combined with S20 and S32. Other inner primer combinations investigated with S3 generated similar assays in Dura, Pisifera and Tenera. The result from this study detects a marker for the Tenera fruit form of the oil palm.